Differential Response of the Photosynthetic Machinery to Fluctuating Light in Mature and Young Leaves of Dendrobium officinale - Yang, Ying-Jie; Shi, Qi; Sun, Hu; Mei, Ren-Qiang; Huang, Wei (Frontiers in Plant Science, 2022)
A key component of photosynthetic electron transport chain, photosystem I (PSI), is susceptible to the fluctuating light (FL) in angiosperms. Cyclic electron flow (CEF) around PSI and water-water cycle (WWC) are both used by the epiphytic orchid Dendrobium officinale to protect PSI under FL. This study examined whether the ontogenetic stage of leaf has an impact on the photoprotective mechanisms dealing with FL. Thus, chlorophyll fluorescence and P700 signals under FL were measured in D. officinale young and mature leaves. Upon transition from dark to actinic light, a rapid re-oxidation of P700 was observed in mature leaves but disappeared in young leaves, indicating that WWC existed in mature leaves but was lacking in young leaves. After shifting from low to high light, PSI over-reduction was clearly missing in mature leaves. By comparison, young leaves showed a transient PSI over-reduction within the first 30 s, which was accompanied with highly activation of CEF. Therefore, the effect of FL on PSI redox state depends on the leaf ontogenetic stage. In mature leaves, WWC is employed to avoid PSI over-reduction. In young leaves, CEF around PSI is enhanced to compensate for the lack of WWC and thus to prevent an uncontrolled PSI over-reduction induced by FL.